2022
DOI: 10.1111/jocd.14934
|View full text |Cite
|
Sign up to set email alerts
|

Giant pilomatrixoma with bullous appearance on the back: A case report and discussion of misdiagnosis

Abstract: Pilomatrixoma is a superficial, benign skin tumor arising from hair follicle matrix cells. 1 It often occurs on the head, face, or neck, 2 rarely on the back or extremities. 3 Its common clinical appearance is a hard, well-circumscribed, slow-growing intradermal nodule covered by the skin of normal appearance or skin whose color has changed secondary to epithelial thinning. 4 In the dermatology and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…reported two cases of cystic pilomatricomas in their study, 4 Yu et al. reported a pilomatricoma with a bullous appearance, 9 and in our study, only one pilomatricoma showed a predominantly cystic composition. This type of pilomatricoma can be easily misdiagnosed.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…reported two cases of cystic pilomatricomas in their study, 4 Yu et al. reported a pilomatricoma with a bullous appearance, 9 and in our study, only one pilomatricoma showed a predominantly cystic composition. This type of pilomatricoma can be easily misdiagnosed.…”
Section: Discussionsupporting
confidence: 55%
“…While pilomatricomas with typical features evaluated using HFUS and CDFI demonstrate excellent diagnostic performance, misdiagnosis frequently occurs for pilomatricomas with atypical sonographic features. These atypical features can resemble other conditions such as infantile hemangioma, trichilemmal cyst, breast cancer, epidermoid cyst, chronic granuloma, and dermatofibrosarcoma protuberans 4–14 . Accurate diagnosis is crucial for appropriate management 15,16 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Clinically, bullous PM needs to be differentiated from lymphangioma, hydrocystoma, epidermal cyst, etc. [ 9 ]. Reviewing previous literature reports [ 10 ], we found the evidence about the inducement of bullous PM, which was associated with the development of anetodermic PM with mechanical trauma.…”
Section: Discussionmentioning
confidence: 99%